Effect of sexual steroids on the calcium content of aortic atherosclerotic plaque of oophorectomized rabbits - Aldrighi,J.M. (2005)
We determined the effect of conjugated equine estrogen plus medroxyprogesterone acetate on calcium content of aortic atherosclerotic lesions in oophorectomized adult New Zealand rabbits submitted to a cholesterol rich diet. Five groups of 10 animals each were studied: G1 = control, G2 = cholesterol diet only, G3 = diet plus conjugated equine estrogen (0.625 mg/day); G4 and G5 = diet, conjugated equine estrogen (0.625 mg/day) plus medroxyprogesterone acetate (5 and 10 mg/day, respectively). Mean weight varied from 2.7 ± 0.27 to 3.1 ± 0.20 kg (P = 0.38) between groups at the beginning and 3.1 ± 0.27 to 3.5 ± 0.20 kg (P = 0.35) at the end of the experiment. Cholesterol and triglyceride levels were determined at the time of oophorectomy, 21 days after surgery (time 0), and at the end of follow-up of 90 days. The planimetric method was used to measure plaque and caryometric method for histopathologic examination of the aorta. Calcium content was determined by the method of von Kossa. A similar increase in cholesterol occurred in all treated groups without differences between them at the end of the study. Groups G4 and G5 had smaller areas of atherosclerotic lesions (2.33 ± 2.8 and 2.45 ± 2.1 cm², respectively) than the groups receiving no progestogens (G2: 5.6 ± 4 and G3: 4.6 ± 2.8 cm²; P = 0.02). The relation between lesion area and total aorta area was smaller in groups treated with combined drugs compared to the groups receiving no progesterone (G4: 14.9 ± 13 and G5: 14.2 ± 13.4 vs G2: 35.8 ± 26 and G3: 25 ± 8 cm², respectively; P = 0.017). Oral conjugated equine estrogen (0.625 mg/day) plus medroxyprogesterone acetate (5 or 10 mg/day) provoked a greater reduction in atherosclerotic plaque area and calcium content in treated groups, suggesting a dose-dependent effect.